A review of clinical and preclinical data supporting a role for resveratrol in the treatment of common respiratory tract pathogens - Giulio Dinardo; Michele Miraglia del Giudice; Lorenzo Drago; Maria Daglia; Alessandra Gori; Attilio Varricchio; Chiara Trincianti; Enrico Tondina; Francesco Paolo Brunese; Giulia Brindisi; Matteo Naso; Anna Maria Zicari; et al. (NFS Journal)
Respiratory infections are a relevant issue during infancy and childhood, constituting a major source of morbidity and imposing a substantial burden on healthcare systems. Conditions such as bronchiolitis, pneumonia, and influenza exemplify the gravity of these infections among pediatric populations. In the context of this health challenge, resveratrol, a naturally occurring polyphenolic antioxidant has emerged as a focal point of extensive research, known for its antioxidant, anti-inflammatory, and antimicrobial properties. This comprehensive review delves into the compound's extensive antimicrobial activities against a diverse range of bacteria and viruses, both as a standalone agent and in combination with conventional antibiotics. This compound exhibits notable antiviral activity against viruses implicated in severe respiratory infections, offering a potential therapeutic avenue. By exploring the antiviral mechanisms and highlighting the anti-inflammatory potential of resveratrol, this comprehensive overview contributes to a deeper understanding of its applicability in mitigating the complexities associated with pediatric respiratory infections.